TECHNICAL METHODS OF CLEANING SHIPWRECKS FROM GHOST NETS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Ghost nets are fishing gear lost and left in bodies of water that continue to be fished. Most of the fishing gear that is lost is made of synthetic materials that break down very slowly or not at all in nature and continue to work long after the net is lost. A ghost net drifts in the sea until it catches on an object, most often a shipwreck. This harms both nature and people's economic interests. Currently, the release of shipwrecks and other sunken objects from fragments of lost nets is mainly done by human hands, resp. divers dive to the wreck and use hand tools to free the wreck from fragments of fishing gear. There are innovative robotic systems in the world that can partially replace the work of divers.